PATHOLOGICAL AND SOME SERUM BIOCHEMICAL EFFECTS INDUCED BY MALATHION IN JAPANESE QUAIL ( C oturnix japonica) - R. Hussain; A. Khan; F. Mahmood (Journal of Animal and Plant Sciences, 2013)
In present experimental study gross, histopathological and different serum biochemical effects of malathion were observed in male Japanese quail. For this purpose apparently active and sexually mature male Japanese quail (approximately 5-6 weeks and each group 15 birds) were kept in six groups (A-F). Malathion @ 0, 25, 50, 75, 100 and 125 mg/kg b.w mixed in corn oil was administered orally for 51 days. Grossly, swollen, edematous and congested lungs, congested kidneys, pale to yellowish, fragile liver and regression of thymus in birds fed malathion (100 and 125 mg/kg b.w) was observed. Histopathological examination revealed mild to moderate cytoplasmic vacuolation in liver and severe pyknosis/condensation in nucleus of kidneys in treated quail (50 and 75 mg/kg b.w) at day 51 of the experiment. However these changes were severe in quail administered higher levels (100 and 125 mg/kg b.w) of organophosphate throughout the experiment. Severer hemorrhage in lungs, thymus and intestine was also observed in birds at higher doses. A significant decrease (P ≤ 0.05) in serum albumin and serum total protein was recorded at higher levels (50, 75, 100 and 125 mg/kg b.w) of malathion. At day 17 of experiment serum creatinine and alanine transaminase was significantly increased in quail given higher levels (125 mg/kg b.w) of malathion. Significantly increased (P ≤ 0.05) values of serum creatinine, aspartate transaminase and alanine transaminase at day 34 and 51 in treated quail (75, 100 and 125 mg/kg b.w) were also recorded. Serum lactate dehydrogenase was significantly increased throughout the experiment at different levels (50, 75, 100 and 125 mg/kg b.w). Malondialdehyde (MDA) contents were also significantly increased in quail. These results provide the first experimental evidence that prolonged and increased levels of malathion induces oxidative stress and tissue changes in birds.
Keywords: Malathion; Quail; Toxicity; Pathology; Serum Biochemistry